Beauty Worshippers Enterprise / Muhammad Haziq Irfan Abdul Shukor... [et al.] - Abdul Shukor, Muhammad Haziq Irfan; Samsudin, Muhamad Yusuf; Azmi, Amirun Izzuddin; Mohamad Murad, Ahmad Nor Aiman; Mohd Sani, Nurul Anis Fadleen (2019)
Beauty Worshippers Enterprise is a new small-sized company that had just operated in Malaysia. It is one of the company that being managed by bumiputera citizens. The name of this company has been inspired by the imagination and aspiration of the partnerships members. It is named Beauty Worshippers since it is a true beauty lover with highest pride that symbolizes strength and power which are the two important criteria to widen and develop our company in this country and nationwide. As for the business, we are producing one of the skin care product that very suitable for Asian especially Malaysian skin types. We understand that customers are usually under great pressure in terms of time, budget, skills and busy with their life. Therefore, we try to establish a bond with customers by giving ideas and advice through the product that we sell to become easier. Besides, we trying to increase the quality of local product compared to the foreign brand. We are starting the business on June 2019 and had five managers that are general manager, administrative manager, operational manager, marketing manager and financial manager. Our target market teenager, both women and men careers and the housewives Based on this survey, Beauty Worshippers Company estimated the market size to be RM 3,661,383.60 a month that is from the teenager, men & women and from the housewives. This estimation was calculated based on 70% from the 131092 people of the population in Shah Alam that was spent for skincare product. Business plan is necessary to all entrepreneurs. It is prepared to a group of people which are owners itself, bankers, suppliers, customers and employees. This plan include in Business Plan chapter which consists of marketing, operation, organization, and financial plan. We believe that we will be able to achieve our business goal with our business financial position statement. We will get our return capital within short time and our current ratio will cover our liabilities and put our business in comfort stage with the highest profit.